2002
DOI: 10.1021/ja011378f
|View full text |Cite
|
Sign up to set email alerts
|

Framework Stability of Nanoporous Inorganic Structures upon Template Extraction and Calcination:  A Theoretical Study of Gallophosphate Polymorphs

Abstract: A systematic computational study of gallophosphates was undertaken. First, lattice energy minimization calculations using a formal-charge shell model potential have been carried out on a series of hypothetical gallium phosphates derived from their metallogallophosphate, aluminophosphate, or aluminosilicate analogues through atomic substitution. The minimized structures show the typical features in terms of bond angles and distances as expected in zeolitic gallophosphates. Second, the crystal structures of seve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 57 publications
1
19
0
Order By: Relevance
“…The framework stability of such solids was estimated by means of computational method using lattice energy minimization calculations. These theoretical studies [77] indicated that the structures are not energetically viable and agree with the experimental data showing the decomposition of the solid after removal of the template.…”
Section: Fluorinated Aluminum or Gallium Phosphatessupporting
confidence: 69%
“…The framework stability of such solids was estimated by means of computational method using lattice energy minimization calculations. These theoretical studies [77] indicated that the structures are not energetically viable and agree with the experimental data showing the decomposition of the solid after removal of the template.…”
Section: Fluorinated Aluminum or Gallium Phosphatessupporting
confidence: 69%
“…The more extensive use of SIESTA in this field is due to Gale and coworkers [144][145][146]. An illustrative example is the study of the binding of palladium atoms and dimers in the zeolite gmelinite.…”
Section: Minerals and Zeolitesmentioning
confidence: 99%
“…For instance, Girard et al [146] have used SIESTA type calculations in order to validate a force field put forward to study the structure of zeolitic gallophosphates. Borowski et al [148] used a combination of experimental and theoretical techniques in order to solve the structure of the layered silicic acid H-RUB-18.…”
Section: Minerals and Zeolitesmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent paper Girard et al [21] have theoretically investigated the stability of a great number of existing and hypothetical gallophosphate structures. However, the authors could not apply their model to cloverite due to the fact that the as-synthesized cloverite framework is interrupted by terminal oxygens (P-OH and Ga-OH groups).…”
Section: Stability Of the Cloverite Structurementioning
confidence: 99%